1962
DOI: 10.1107/s0365110x62001395
|View full text |Cite
|
Sign up to set email alerts
|

Refinement of the structure of metastable phosphonitrilic chloride, (PNCl2)4

Abstract: The crystal structure of (PNC12) 4 has been refined by three-dimensional Fourier syntheses. The crystallographically non-equivalent P-I~ bonds in the puckered eight-membered ring have an equal length of 1.570 A, s.d. 0.01 A. The average value for the P-C1 bond lengths is 1.989/~, s.d. 0.004 A. The configuration of the molecule is compatible with Craig's or Dewar's theory in which a delocalization of the p-z and d-z electrons is assumed. IntroductionIn an early structure determination of the metastable modifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

1962
1962
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(26 citation statements)
references
References 3 publications
3
23
0
Order By: Relevance
“…Additionally, it was shown before 67 that puckered shape of cyclooctatetraene C 8 H 8 takes planar shape for its negative dianion C 8 H 8 −2 . For the phosphazenes ͑NPX 2 ͒, while N 4 P 4 F 8 is planar N 4 P 4 Cl 8 and N 4 P 4 ͑CH 3 ͒ 8 have buckled shapes 68,69 and thus the rule regarding the compounds including first row elements is still valid.…”
Section: Planar Puckeredmentioning
confidence: 99%
“…Additionally, it was shown before 67 that puckered shape of cyclooctatetraene C 8 H 8 takes planar shape for its negative dianion C 8 H 8 −2 . For the phosphazenes ͑NPX 2 ͒, while N 4 P 4 F 8 is planar N 4 P 4 Cl 8 and N 4 P 4 ͑CH 3 ͒ 8 have buckled shapes 68,69 and thus the rule regarding the compounds including first row elements is still valid.…”
Section: Planar Puckeredmentioning
confidence: 99%
“…Two crystal modifications of this compound, generally called the K and T forms, are known (Hazekamp, Migchelsen & Vos, 1962;Wagner & Vos, 1968). The crystal structures of some NaP4C18 derivatives such as cis-N4PaC14Ph4 (Bullen & Tucker, 1972a), ~-trans-NaP4C14(NMe2)4 (Bullen & Tucker, 1972b), ~-trans-N4Pn(NHMe)4Ph4 (Bullen & Mallinson, 1972), NaPaC14(NEt2)4 (Hrkelek & Kah (, 1990) and NaP4C17(NPPh3) (Babu & Manohar, 1979) have been examined.…”
mentioning
confidence: 99%
“…Figures 1-3 show the structures of three cyclic phosphazenes. The crystallographic data [1][2][3][4] reported that the P-N-P angles takes different values. In addition, in each ring of 2 and 4 this valence angle varies.…”
Section: Force Field Implementationmentioning
confidence: 99%
“…The crystal structure of (NPCl 2 ) 3 is known to correspond to a planar conformation [1] while (NPCl 2 ) 4 exists in two different crystalline conformations [2,3], the S 4 skew tub and the C i skew chair forms, respectively. The crystalline form of (NPCl 2 ) 5 [4] adopts the indented nearly planar conformation.…”
Section: Introductionmentioning
confidence: 99%